Model Kebijakan Pemerintah Desa Dalam Penguatan Pendidikan Non Formal Keagamaan Untuk Pemberdayaan Masyarakat - Dwi Noviani; Hilmin Hilmin; Elhefni Elhefni; Mustafiyanti Mustafiyanti (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
Strengthening non-formal religious education is an important aspect in efforts to empower village communities. Village governments have a central role in designing policy models that focus on strengthening religious education at the local level. In this research, a qualitative approach was used, taking data from various sources through library research. The research results found that village government policies in implementing non-formal education include several key aspects including community participation, partnerships with religious institutions, provision of adequate facilities and resources budgeted in the APBDes, as well as integration with formal education. Community participation in planning and implementing non-formal religious education programs directs programs that are more relevant to local needs and more supported by the community, because these policies are based on participatory principles and are a joint commitment between the community and the village government as stated in the RPJMDes and RKPDes policy documents. Establishing partnerships with religious institutions is a strong basis for supporting and integrating non-formal religious education in villages. Because formal religious institutions which are also managed by the government have human resources who are trained in the field of religion and can become teachers or facilitators in non-formal religious education activities, due to the weaknesses and limitations of human resources in the village. Next, providing adequate facilities and resources is a prerequisite for creating a conducive learning environment. The availability of classrooms, learning facilities, books and adequate operational funds will improve the quality of non-formal religious education in the village. Integration with formal education is also an important step in strengthening non-formal religious education. Collaboration between formal and non-formal education creates a learning environment that is holistic and relevant to students' needs. Through this policy model, strengthening non-formal religious education in villages can empower the community and increase their knowledge, skills and religious awareness. Continuous evaluation and monitoring are important tools in measuring program effectiveness and ensuring the continuity of community empowerment efforts through religious education at the village level. Keywords; Village Government Policy Model, Non-Formal Religious Education, Community Empowerment